1990
DOI: 10.1021/jm00163a051
|View full text |Cite
|
Sign up to set email alerts
|

4-(1,2,5,6-Tetrahydro-1-alkyl-3-pyridinyl)-2-thiazolamines: a novel class of compounds with central dopamine agonist properties

Abstract: The design, synthesis, and pharmacological properties of a novel type of 4-(1,2,5,6-tetrahydro-1-alkyl-3-pyridinyl)-2-thiazolamine with dopaminergic properties are described. In particular, 4-(1,2,5,6-tetrahydro-1-propyl-3-pyridinyl)-2-thiazolamine (4c, PD 118440) and its allyl analogue (4i, PD 120697) have been identified as orally active dopamine (DA) agonists with pronounced central nervous system effects in tests that include [3H]-haloperidol and [3H]-N-propylnorapomorphine binding, inhibition of striatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(98 citation statements)
references
References 3 publications
0
96
0
2
Order By: Relevance
“…Free radicals and reactive sulfur species such as thiol radicals are frequently synthesized through many biological processes and may be considered as indicators of biological inadequacy. In recent times, the applications of thiazoles have found in drug development for the treatment of allergies 6 , hypertension, 7 inflammation, 8 schizophrenia, 9 bacterial, 10 HIV infections, 11 and hypnotics 12 . Moreover, thiazoles have been used for the treatment of pain, 13 as fibrinogen receptor antagonists with antithrombotic activity 14 and as new inhibitors of bacterial DNA gyrase B.…”
Section: Introductionmentioning
confidence: 99%
“…Free radicals and reactive sulfur species such as thiol radicals are frequently synthesized through many biological processes and may be considered as indicators of biological inadequacy. In recent times, the applications of thiazoles have found in drug development for the treatment of allergies 6 , hypertension, 7 inflammation, 8 schizophrenia, 9 bacterial, 10 HIV infections, 11 and hypnotics 12 . Moreover, thiazoles have been used for the treatment of pain, 13 as fibrinogen receptor antagonists with antithrombotic activity 14 and as new inhibitors of bacterial DNA gyrase B.…”
Section: Introductionmentioning
confidence: 99%
“…Thiazole derivatives have been extensively studied and so far, a variety of biological activities have been reported, for a large number of their derivatives, such as antihypertensive, anti-inflammatory, antischizophrenia, antibacterial, anti-HIV, hypnotics, antiallergic, analgesic, fibrinogen receptor antagonist, bacterial DNA gyrase B inhibitor and antitumor activities. [10][11][12][13][14][15][16][17][18][19][20][21][22] Also they have wide range of applications in organic functional materials such as fluorescent dyes 23 and liquid crystals.…”
Section: -9mentioning
confidence: 99%
“…Monoindole and bisindole have been intensively studied and the results revealed that most of them have biological activities; for example, indole-3-carbinol, found in Brassica plants, is a potential cancer protective agent [5,6]. Thiazoles can be found in drug development for the treatment of allergies [7], hypertension [8], inflammation [9], schizophrenia [10], bacterial infections [11], HIV [12], sleep disorders [13], and for the treatment of pain [14], as fibrinogen receptor antagonists with antithrombotic activity [15] and as new inhibitors of bacterial DNA gyrase B [16]. The 1,2,4-triazolopyrimidines have also attracted growing interest due to their important pharmacological activities, such as antitumor, antimalarial, antimicrobial, anti-inflammatory, and antifungal activity, as well as macrophage activation [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%